2017
DOI: 10.1002/cnma.201700149
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Fields Focused to Molecular Size

Abstract: Efficient use of light energy is regarded as a key factor in solving energy challenges to create a sustainable society. The highly concentrated photon energy generated by localized surface plasmon resonance excitation in the vicinity of metal nanostructures can enhance light‐matter interaction. Optimization of the interactions between plasmons and electrons in materials can lead to novel light energy applications. To overcome the current limitations for these interactions, the plasmon field must be focused to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 115 publications
(298 reference statements)
0
6
0
Order By: Relevance
“…In general, multipolar absorption is inherently small because it ensues from the electromagnetic field spatial variation within the molecule 19 . However, over recent years it has been shown that such "forbidden" transitions can be accessed by the deepsubwavelength scattered field produced by graphene nanostructures [47][48][49][50][51][52][53][54][55] . Note in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…In general, multipolar absorption is inherently small because it ensues from the electromagnetic field spatial variation within the molecule 19 . However, over recent years it has been shown that such "forbidden" transitions can be accessed by the deepsubwavelength scattered field produced by graphene nanostructures [47][48][49][50][51][52][53][54][55] . Note in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Under the excitation of the LSPR, the strong electric field forms in the vicinity of the metal nanostructure depending on the size or shape of the structure and can induce various unique chemical phenomena. [4][5][6][7] Especially, the strong coupling between the energy quanta in matter, such as the exciton, vibration, or intraband transition, and plasmons has been recognized as the important phenomena because it can modify the property of the materials in exotic way. [8][9][10][11][12][13][14] Under the formation of the strong coupling regime, the energy is coherently exchanged between electrons and plasmons showing new energy hybridized states, which are the upper and lower polaritons form.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that surface-enhanced Raman scattering (SERS) observation can be used as the very efficient tool for probing the molecular behavior at interfaces. The enhancement of Raman scattering can be described as the excitation of the localized surface plasmon resonance (LSPR) at the metal nanostructures. It has been recognized that the SERS spectrum is the result of the specific interaction between LSPR and molecules. It could be very important to discuss about the information on adsorbed states of molecules to affect the resonant electronic excitation as a result of the electronic interactions .…”
Section: Introductionmentioning
confidence: 99%